1997
DOI: 10.1143/jjap.36.l394
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Homojunction Using Spray Pyrolised CdS Thin Film by Copper Diffusion

Abstract: We continue to investigate possible signatures of a pre-inflationary anisotropic phase in two-point and three point correlation functions of the curvature perturbation for high-momentum modes which exit the horizon well after isotropization. The late time dynamics of these modes is characterized by a non-Bunch Davies vacuum state which encodes all the information about initial anisotropy in the background space-time. We observe that, unlike the non-planar momenta, there exist regimes of planar momenta for whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This selenium film was used for the selenization process. In our laboratory, over the past several years we have been able to deposit different semiconducting chalcogenide films, such as CdS [8], CuInSe 2 [9], Cu 3 Se 2 [10] and CuInS 2 [11], using the CBD technique. This expertise is used for the preparation of the selenium thin film.…”
Section: Introductionmentioning
confidence: 99%
“…This selenium film was used for the selenization process. In our laboratory, over the past several years we have been able to deposit different semiconducting chalcogenide films, such as CdS [8], CuInSe 2 [9], Cu 3 Se 2 [10] and CuInS 2 [11], using the CBD technique. This expertise is used for the preparation of the selenium thin film.…”
Section: Introductionmentioning
confidence: 99%
“…The n-type CdS thin films (with a thickness of 2-3 µm and dimensions of about 8 × 8 mm) were obtained on glass and In-coated glass substrates by vacuum-evaporation in a quasi-closed volume [8,9]. The temperature of the substrates was 250 • C. The resistivity of as-grown n-type CdS films was about 4×10 7 Ohm cm −1 . Two closely-spaced semitransparent Cu films in circular form were deposited onto the upper surface of the CdS film by vacuum evaporation.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of p-n homojunction in spray pyrolized CdS thin film by thermal § Permanent address: Institute of Physics, Azerbaijan Academy of Sciences, 370143 Baku, Azerbaijan. annealing of nCdS/Cu bilayer structures was reported in [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…Very recently it was reported that the fabrication of p-n homojunctions is possible in CdS and ZnO. Fabrication of homojunction solar cells in CdS was made possible using spray pyrolysis coupled with vacuum evaporation [1,2]. Copper was deposited over the n-CdS thin film and the bilayer was annealed at a temperature of 300 • C under high vacuum.…”
Section: Introductionmentioning
confidence: 99%